THE ROLE OF HR IN MANAGING QUIET QUITTING AND EMPLOYEE DISENGAGEMENT IN GEN Z EMPLOYEES OF TELECOM SECTOR - Ijaz Ahmed; Dr. Muhammad Asif (Policy Journal of Social Science Review, 2026)
This study explores the contribution of Human Resource Management (HRM) in combating the phenomenon of Quiet Quitting and Work Engagement among Generation Z employees in Pakistan's Telecommunications industry. The study adopted the quantitative cross sectional type of design to collect data from 270 employees of telecom organizations in Pakistan. In the study, validated scales to measure quiet quitting, job satisfaction, organizational commitment, work-life balance, and HR practices were used. SPSS was used for data analysis which included correlation and regression analyses. The results show that job satisfaction (β = -0.358, p < 0.001) and work-life balance (β = -0.134, p < 0.05) significantly negatively predict quiet quitting, while organizational commitment has a non-significant direct effect (β = -0.103, p = 0.090). HR practices such as flexible work policies, recognition policies, and career development opportunities proved to be key moderators. The model accounted for 30% of variance in quiet quitting behaviours. Job satisfaction is paramount for telecom companies, which can be achieved through fair compensation, accolades and work-life balance programs. HR should adopt flexible working options, mental health assistance and career development paths that are tailored to the expectations of Gen Z. The study is one of the initial studies which was done quantitatively to explore the phenomenon of ‘quiet quitting' among the Gen Z employees in the Pakistan context by incorporating multiple theories. Keywords: Quiet Quitting, Gen Z, Employee Disengagement, Human Resource Management, Telecom Sector, Job Satisfaction, Work-Life Balance